The metal hyperaccumulators from New Caledonia can broaden our understanding of nickel accumulation in plants - Jaffré, Tanguy; Pillon, Yohan; Thomine, Sébastien; Merlot, Sylvain (Frontiers in Plant Science, 2013)
While an excess of metals such as zinc, cadmium or nickel (Ni) is toxic for most plants, about 500 plant species called hyperaccumulators are able to accumulate high amounts of these metals. These plants and the underlying mechanisms are receiving an increasing interest because of their potential use in sustainable biotechnologies such as biofortification, phytoremediation and phytomining. Among hyperaccumulators, about 400 species scattered in 40 families accumulate Ni. Despite this wide diversity, our current knowledge of the mechanisms involved in Ni accumulation is still limited and mostly restricted to temperate herbaceous Brassicaceae. New Caledonia is an archipelago of the tropical southwest pacific with a third of its surface (5500 km2) covered by Ni-rich soils originating from ultramafic rocks. The rich New Caledonia flora contains 2145 species adapted to these soils, among which 65 are Ni hyperaccumulators, including lianas, shrubs or trees, mostly belonging to the orders Celastrales, Oxalidales, Malpighiales and Gentianales. We present here our current knowledge on Ni hyperaccumulators from New Caledonia and the latest molecular studies developed to better understand the mechanisms of Ni accumulation in these plants.